Effect of Financial Inclusion on Economic Development and Community Welfare in East Kalimantan Province - Susanti Susanti; Eny Rochaida; Diana Lestari (Budapest International Research and Critics University, 2022)
The research objective is to explore effect of financial inclusion on economic development and community welfare in East Kalimantan Province. This research is a quantitative research. Data retrieval takes the object of research in East Kalimantan Province, by taking secondary data from related agencies such as the Financial Services Authority, the Central Statistics Agency of East Kalimantan Province, as well as other data sources that are considered to be able to support the writing of this thesis. The data used is secondary data in the form of time series for a period of fifteen years, namely from 2007 to 2021. Data collection techniques used from research are in the form of library research and recording. Data analysis in this study is carry out using multiple regression analysis. The results of the study show that financial inclusion has a positive and significant effect on economic development in East Kalimantan Province. Financial inclusion has a positive and significant effect on community welfare in East Kalimantan Province. Economic development has a negative and significant effect on community welfare in East Kalimantan Province. Financial inclusion has a negative and unsignificant effect on community welfare through economic development in East Kalimantan Province.